2013
DOI: 10.5888/pcd10.130016
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Outcomes of a Chronic Disease Self-Management Program for Spanish-Speaking Older Adults in South Florida, 2008–2010

Abstract: IntroductionThe prevalence and negative health effects of chronic diseases are disproportionately high among Hispanics, the largest minority group in the United States. Self-management of chronic conditions by older adults is a public health priority. The objective of this study was to examine 6-week differences in self-efficacy, time spent performing physical activity, and perceived social and role activities limitations for participants in a chronic disease self-management program for Spanish-speaking older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…The differences between Hispanic and non-Hispanic and by level of comorbidity were the largest. Previous studies have shown greater difficulty in disease management among Hispanics, perhaps due to language and cultural barriers, lack of access to preventive services, lack of insurance, and greater medical comorbidity[42]. The mean SEMCD6 rating for the Hispanic sample in this study is similar to those reported in two randomized controlled trials of disease management among Hispanics[42].…”
Section: Discussionsupporting
confidence: 72%
“…The differences between Hispanic and non-Hispanic and by level of comorbidity were the largest. Previous studies have shown greater difficulty in disease management among Hispanics, perhaps due to language and cultural barriers, lack of access to preventive services, lack of insurance, and greater medical comorbidity[42]. The mean SEMCD6 rating for the Hispanic sample in this study is similar to those reported in two randomized controlled trials of disease management among Hispanics[42].…”
Section: Discussionsupporting
confidence: 72%
“…Structured self-management programmes have been shown to improve a wide range of outcomes in older adults. Improvements have been observed in physical activity, 27 29 self-care, 27 chronic pain 30 and self-efficacy. 27 30 …”
Section: Who’s Approachmentioning
confidence: 99%
“…The conceptual model in this study was based on the chronic care model launched by Wagner and colleagues in 1999 19. The chronic care model has been considered to be an effective framework for improving the quality of diabetes care 20. This model includes six core elements for the provision of optimal care of patients with chronic diseases 21.…”
Section: Conceptual Framework For the Studymentioning
confidence: 99%